Acceptability and Utility of an Innovative Feeding Toolkit to Improve Maternal and Child Dietary Practices in Bihar, India. (March 2015) - Collison, Deborah Kortso; Kekre, Priya; Verma, Pankaj; Melgen, Sarah; Kram, Nidal; Colton, Jonathan; Blount, Wendy; Girard, Amy Webb
Background: Dietary practices in India often fail to provide adequate nutrition during the first 1, 000 days of life. Objective: To explore the acceptability and utility of a low-cost and simple-to-use feeding toolkit consisting of a bowl with marks to indicate meal volume and frequency, a slotted spoon, and an illustrated counseling card to cue optimal dietary practices during the first 1, 000 days. Methods: In Samastipur District, Bihar, India, we conducted 16 focus group discussions and 8 key informant interviews to determine community acceptability and obtain feedback on design and delivery of the feeding toolkit. We conducted 14 days of user testing with 20 pregnant women, 20 breast-feeding women 0 to 6 months postpartum, and 20 mothers with infants 6 to 18 months of age. Results: The toolkit, which is made of plastic, was well accepted by the community, although the communities recommended manufacturing the bowl and spoon in steel. The proportion of pregnant and breast-feeding women taking an extra portion of food per day increased from 0% to 100%, and the number of meals taken per day increased from two or three to three or four. For children 6 to 18 months of age, meal frequency, quantity of food consumed during meals, and thickness of the foods increased for all age groups. Children 6 to 8 months of age who had not yet initiated complementary feeding all initiated complementary feeding during the testing period. Conclusions: Simple feeding tools are culturally acceptable and can be appropriately used by families in Bihar, India, to improve dietary practices during the first 1, 000 days of life. Research is needed to assess whether the tools promote dietary and nutritional improvements over and above counseling alone.